2003
DOI: 10.1021/jp030398w
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigations into the Structural and Electronic Influences on the Hydrogen Bonding in Doped Polyaniline

Abstract: DFT-based electronic structure calculations are performed on a series of compounds designed to model the hydrogen bonding present in sulfonic acid-doped polyaniline. A thorough investigation of the structural and electronic influences on the hydrogen bonding at the B3LYP/6-311++G(2d,2p) level reveals a number of previously unknown features of such systems. Rearrangements of both the geometry and electronic configuration indicate that the creation of a hydrogen bond between the N-H group in the polyaniline mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
31
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(35 citation statements)
references
References 25 publications
4
31
0
Order By: Relevance
“…Similar calculations are performed on aniline for comparison purposes. This particular combination of functional and basis set is widely accepted as being applicable to such systems and has been successfully used recently on very similar compounds [20]. We note that a complete description of r-conjugation would require an examination into how the amount of HF exchange in the hybrid functionals affects the accuracy of the data [29].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar calculations are performed on aniline for comparison purposes. This particular combination of functional and basis set is widely accepted as being applicable to such systems and has been successfully used recently on very similar compounds [20]. We note that a complete description of r-conjugation would require an examination into how the amount of HF exchange in the hybrid functionals affects the accuracy of the data [29].…”
Section: Methodsmentioning
confidence: 99%
“…Previous work by this group on the structural and electronic effects on the hydrogen bonding in doped PANi [20] concluded that the creation of a hydrogen bond between the polymer and its dopant increases the ability of the PANi backbone to conduct. That analysis is very similar in methodology to work presented here, and the two papers can be considered complimentary.…”
Section: Introductionmentioning
confidence: 99%
“…49 In addition, this hypothesis was backed up by density functional theory calculations on a semiconducting polymer. 50 Furthermore, in a study on oriented LEPs ͑MEH-PPV͒ in a nanoscale architecture it was observed that the electronic energy transfer is more efficient between individual polymer chains then along the chain. 51 As the rate of energy transfer is directly related to the coupling strength 52 the conclusion of that study is that interchain interactions are stronger than the intrachain interactions.…”
Section: Circular Dichroismmentioning
confidence: 99%
“…The theoretical investigations dedicated to PANI are also plentiful and cover almost all computational levels, i.e., molecular mechanics and dynamics [17] (doping mechanism, proton migration, temperature dependence of absorption, and conductivity), Monte Carlo [18,19] (interchain electronic transport in disordered systems), Hü ckel [20] (band structure, DOS), semi-empirical methods [21,22] (structure, UV/VIS spectra), as well as firstprinciple methods such as Hartree-Fock and DFT [23][24][25][26][27][28] (structure, infrared and Raman spectra). Some semi-empirical calculations are performed for the evaluation of torsion barriers and solvation effects on the UV/VIS spectra of PANI chains, accounted for by models including 2 to 4 solvent molecules [29,30].…”
Section: Introductionmentioning
confidence: 99%